Mejoramiento eje vial Avenida Illanes-Freire, Rancagua - ICR Consultores (Chile, Santiago, 1991)
V.1: Informe Final. V.2: Anexos
Keywords: MEJORAMIENTO VIAL; CHILE; RANCAGUA; REGION DEL LIBERTADOR GENERAL BERNARDO O HIGGINS; ESTUDIOS BASICOS 1991; AVENIDA ILLANES; CALLE FREIRE; CODIGO BIP 20024244-0; CONSULTORIA REGION DEL LIBERTADOR GENERAL BERNARDO O'HIGGINS; DETERIORO DE PAVIMENTOS